Bracing for heat and humidity amidst new challenges in Tokyo - Vanos, J. K.; Thomas, W. M.; Grundstein, A. J.; Hosokawa, Y.; Casa, D. J. (Temperature, 2021)
Comment on: Vanos, J. K., Thomas, W. M., Grundstein, A. J., Hosokawa, Y., Liu, Y., & Casa, D. J. (2020). A multi-scalar climatological analysis in preparation for extreme heat at the Tokyo 2020 Olympic and Paralympic Games. Temperature, 7(2), 191-214. DOI: https://doi.org/10.1080/23328940.2020.1737479 SPONET ID. 4071597